2004
DOI: 10.1080/02699050310001657394
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the stroke drivers screening assessment for people with traumatic brain injury

Abstract: Cognitive impairments resulting from brain injury affect driving performance. The question of fitness to drive often arises during rehabilitation. Healthcare professionals need reliable criteria against which decisions about driving fitness can be made. Nouri et al. developed the Stroke Drivers Screening Assessment (SDSA), which was found predictive of on-road driving performance in stroke patients. The purpose of this study was to determine whether the SDSA, either alone or combined with other tests, predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 19 publications
1
43
1
1
Order By: Relevance
“…The DBOG (Driving Behaviours Observation Grid) is a driving performance evaluation (unpublished) that was developed for a research project on the neuropsychological assessment of older drivers. Based on a literature review of studies with road tests for people with cognitive disabilities (Akinwuntan et al, 2003;De Raedt and Ponjaert-Kristoffersen, 2001;Fitten et al, 1995;Hunt et al, 1997;Janke and Eberhard, 1998;Radford, 2001), the present version was developed with the consensus of two independent experts on driving examinations. To develop a valid driving assessment for older people, the driving habits and difficulties that previous research found for this group (Ferreira et al, 2007) were also taken into account.…”
Section: Instrumentsmentioning
confidence: 99%
“…The DBOG (Driving Behaviours Observation Grid) is a driving performance evaluation (unpublished) that was developed for a research project on the neuropsychological assessment of older drivers. Based on a literature review of studies with road tests for people with cognitive disabilities (Akinwuntan et al, 2003;De Raedt and Ponjaert-Kristoffersen, 2001;Fitten et al, 1995;Hunt et al, 1997;Janke and Eberhard, 1998;Radford, 2001), the present version was developed with the consensus of two independent experts on driving examinations. To develop a valid driving assessment for older people, the driving habits and difficulties that previous research found for this group (Ferreira et al, 2007) were also taken into account.…”
Section: Instrumentsmentioning
confidence: 99%
“…The SDSA was designed and validated for stroke patients and later on for TBI patients Radford, Lincoln, & Murray-Leslie, 2004), but in Sweden it is often used clinically to assess different and mixed diagnostic groups, as in this study (Larsson et al, 2007). Another limitation in the present study is the relatively small number of subjects in each diagnostic group, especially the TBI and Other groups.…”
Section: Discussionmentioning
confidence: 99%
“…9,15,16,22,23 The reliability and validity of the different versions of the battery as a good predictor of driving performance after stroke have been established. 16,18,24,25 The accuracy and sensitivity of predicting the road performance (the main outcome measure) using the equation based on the study sample (86% and 80%, …”
Section: Discussionmentioning
confidence: 99%